2007
DOI: 10.1162/qjec.122.1.337
|View full text |Cite
|
Sign up to set email alerts
|

On Committees of Experts

Abstract: A committee makes a decision on a project on behalf of "the public." Members of the committee agree on the a priori value of the project, and hold additional private information about its consequences. They are experts who care about the value of the project and about being considered well informed. Before voting on the project, members can exchange their private information simultaneously. We show that reputational concerns make the a priori unconventional decision more attractive and lead committees to show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Contrary to cheap-talk deliberation, where the set of available messages does not vary with individuals' private information (e.g., Austen-Smith and Feddersen 2005, 2006; Coughlan 2000; Doraszelski, Gerardi, and Squintani 2003; Gerardi and Yariv 2007; Levy 2007; Meirowitz 2006, 2007; and Visser and Swank 2007), Axiom 2 formalizes the assumption that any individual can provide evidence for the signal that she privately observed. By reporting a particular message that is available only for a given signal, an individual proves to the committee that she observed that signal.…”
Section: Model and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to cheap-talk deliberation, where the set of available messages does not vary with individuals' private information (e.g., Austen-Smith and Feddersen 2005, 2006; Coughlan 2000; Doraszelski, Gerardi, and Squintani 2003; Gerardi and Yariv 2007; Levy 2007; Meirowitz 2006, 2007; and Visser and Swank 2007), Axiom 2 formalizes the assumption that any individual can provide evidence for the signal that she privately observed. By reporting a particular message that is available only for a given signal, an individual proves to the committee that she observed that signal.…”
Section: Model and Resultsmentioning
confidence: 99%
“… 5 In contrast to our article, all models of deliberation assume a cheap-talk debate (see also, e.g., Gerardi and Yariv 2007, Levy 2007, Meirowitz 2006, 2007, and Visser and Swank 2007). Two exceptions are Bade and Rice (2007), who study the incentives for information acquisition voters prior to deliberation, and Schulte 2010, who studies the impact of information environments on full information aggregation.…”
mentioning
confidence: 91%
“…Uncertain level of judgment has not been frequently modeled in the jury literature. Recent related work includes Visser and Swank (2007).…”
Section: A Uncertainty About Mpc Members' Judgmentmentioning
confidence: 99%
“…Meade and Stasavage (2008) show that a publication of material that allows for identifying individual opinions (such as transcripts) creates strong incentives for committee members (who also care about their reputation) to present a united front to the outside world. This is because an agreement makes them appear more knowledgeable (see also Swank et al, 2007).…”
Section: Empirical Evidencementioning
confidence: 99%
“…Studying this setup, we link the previous delegation literature to the literature on decision making in committees of careerist experts. Most of the papers in this literature consider the case of costless information (e.g., Levy 2007a, b;Visser and Swank 2007;Gersbach and Hahn 2008;Mattozzi and Nakaguma 2017;Fehrler and Hughes 2018) with two exceptions (Gersbach andHahn 2012, Swank and. None of them studies the decision to delegate a task to a committee, which is the focus of our study.…”
Section: Introductionmentioning
confidence: 99%